Цифрові інструменти маркетингових досліджень як резерв підвищення результативності маркетингової діяльності - Ларка, Людмила Сергіївна (ТОВ "ДКС Центр", 2026)
Систематизовано сучасні тенденції у проведенні маркетингових досліджень, обумовлені поширенням цифрових технологій. Метою статті є висвітлення взаємозв’язку між маркетинговими дослідженнями, маркетинговою інформаційною системою та результативністю маркетингової діяльності. Проведено порівняльний аналіз застосування онлайн та оффлайн форм маркетингових досліджень кон’юнктури ринку, конкурентного середовища, поведінки споживачів, прогнозних досліджень збуту та досліджень брендів. Визначено цифрові сервіси, які доцільно застосовувати для проведення опитувань респондентів, автоматизованих спостережень, експериментів. Показано, що маркетингові дослідження забезпечують ефективність маркетингової діяльності за рахунок діагностування наявного та потенційного попиту на продукцію, дослідження рівня конкурентоспроможності товарів та послуг. Встановлено, що внесок маркетингових досліджень у забезпечення ефективності маркетингової діяльності полягає у підвищенні точності прогнозування обсягів реалізації продукції, підвищенні точності побудови портретів споживачів.

The article systematizes current trends in marketing research, driven by the spread of digital technologies. The aim of the article is to highlight the relationship between marketing research, marketing information systems, and marketing performance. A comparative analysis of the use of online and offline forms of marketing research on market conditions, the competitive environment, consumer behavior, sales forecasting research, and brand research was conducted. Digital services that are appropriate to use for conducting surveys of respondents, automated observations, and experiments have been identified. It is shown that marketing research ensures the effectiveness of marketing activities by diagnosing the existing and potential demand for products, studying the level of competitiveness of goods and services. It has been established that the contribution of marketing research to ensuring the effectiveness of marketing activities lies in increasing the accuracy of forecasting product sales volumes and increasing the accuracy of constructing consumer portraits. Structuring information within a marketing information system simplifies data verification procedures for accuracy and reliability. In addition, it directly affects the level of economic security of the enterprise, since limiting access to certain information prevents its leakage outside the organization. It is shown that the positive consequences of using the results of marketing research within the marketing information system are timely adjustment of the production program, more efficient use of its resources, increasing the efficiency of product, pricing, sales and communication policies, minimizing marketing risks, increasing the profitability of the marketing and business activities of the enterprise as a whole, improving its strategic set. It is shown that the key features of modern marketing research are simplification of communication with respondents, application of artificial intelligence algorithms, social media analytics, use of blockchain technologies. Digital marketing research tools are very diverse and allow you to increase the efficiency of conducting marketing research by increasing the accuracy of substantiating the sample size, the quality of developing survey forms, reducing errors when processing respondent responses, etc.
Digital marketing research tools as a reserve for improving the performance of marketing activities
Keywords: маркетингові дослідження; цифровізація; маркетингова інформаційна система; респонденти; інформація; штучний інтелект; marketing research; digitalization; marketing information system; respondents; information; artificial intelligence